Climate Change and Food Insecurity - Bryant, Christopher Robin; Vitali, Andrea; Madani, Azzeddine (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint presents a collection of twelve scientific articles that delve into the complex relationship between climate change and food security in various regions of the world. The articles examine the impact of climate change on crop production, water resources, and livestock farming, and they explore potential adaptive measures to mitigate the effects of climate change on food security. The articles cover a wide range of geographic locations, from Southeastern Poland to Central Ethiopia, Algeria, Egypt, South Africa, Afghanistan, and Canada. Each article provides valuable insight into the impact of climate change on food security, including the potential link between drought and wild blueberry production in Maine, the use of geospatial assessments to guide climate adaptation strategies for flood-tolerant rice varieties in India, and the impact of non-conventional agricultural spaces on mitigating the effects of climate change on food security in Quebec, Canada. The authors also explore the impact of climate-smart agriculture interventions on food security and dietary diversity in Myanmar, as well as the determinants of smallholder livestock farmers' household resilience to food insecurity in South Africa. Additionally, the reprint includes a case study on water profitability analysis to improve food security and climate resilience in the Egyptian Nile Delta. Taken together, these articles provide a comprehensive understanding of the impact of climate change on food security and highlight the need for innovative solutions to ensure sustainable food systems in the face of climate change.